Postprandial oxytocin secretion is associated with severity of anxiety and depressive symptoms in anorexia nervosa - Lawson, Elizabeth A. (2013)
OBJECTIVE: Anorexia nervosa, a psychiatric disorder characterized by self-induced starvation, is associated with endocrine dysfunction and comorbid anxiety and depression. Animal data suggest that oxytocin may have anxiolytic and antidepressant effects. We have reported increased postprandial oxytocin levels in women with active anorexia nervosa (AN), and decreased levels in weight-recovered women with anorexia nervosa (ANWR) compared to healthy controls (HC). A meal may represent a significant source of stress in patients with disordered eating. We therefore investigated the association between post-prandial oxytocin secretion and symptoms of anxiety and depression in anorexia nervosa. METHOD: We performed a cross-sectional study of 35 women (13 AN, 9 ANWR and 13 HC). Serum oxytocin and cortisol and plasma leptin levels were measured fasting and 30, 60, and 120min after a standardized mixed meal. The area under the curve (AUC), and for oxytocin, postprandial nadir and peak levels were determined. Anxiety and depressive symptoms were assessed using the Spielberger State-Trait Anxiety Inventory (STAI) and Beck Depression Inventory II (BDI-II). RESULTS: In women with anorexia nervosa, oxytocin AUC and post-prandial nadir and peak levels were positively associated with STAI scores. Oxytocin AUC and nadir levels were positively associated with BDI-II scores. After controlling for cortisol AUC, most relationships remained significant. After controlling for leptin AUC, all of the relationships remained significant. Oxytocin secretion explained up to 51% of the variance in STAI trait and 24% of BDI-II scores. CONCLUSIONS: Abnormal post-prandial oxytocin secretion in women with anorexia nervosa is associated with increased symptoms of anxiety and depression. This may represent an adaptive response of oxytocin secretion to food-related symptoms of anxiety and depression.